2021
DOI: 10.3390/foods10081757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ultra-High-Pressure Homogenization of Buttermilk for the Production of Yogurt

Abstract: Despite its nutritional properties, buttermilk (BM) is still poorly valorized due to its high phospholipid (PL) concentration, impairing its techno-functional performance in dairy products. Therefore, the objective of this study was to investigate the impact of ultra-high-pressure homogenization (UHPH) on the techno-functional properties of BM in set and stirred yogurts. BM and skimmed milk (SM) were pretreated by conventional homogenization (15 MPa), high-pressure homogenization (HPH) (150 MPa), and UHPH (300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
6
2
Order By: Relevance
“…It did not agree with what was found by [3]. which found that the percentage of protein is 1.3%, and fat is 0.8%.With what was mentioned by [21], the percentage of protein and fat in buttermilk is 4.28 and 0.59%. It was shown [1] that MFGM proteins represent about 19% of the milk proteins that have biologically active properties, and the mixing process caused their breakdown, which affected the proportion of proteins [22].…”
Section: Ph Surface Titration Acidity and Chemical Contentcontrasting
confidence: 81%
See 1 more Smart Citation
“…It did not agree with what was found by [3]. which found that the percentage of protein is 1.3%, and fat is 0.8%.With what was mentioned by [21], the percentage of protein and fat in buttermilk is 4.28 and 0.59%. It was shown [1] that MFGM proteins represent about 19% of the milk proteins that have biologically active properties, and the mixing process caused their breakdown, which affected the proportion of proteins [22].…”
Section: Ph Surface Titration Acidity and Chemical Contentcontrasting
confidence: 81%
“…Against Enterococcus faecalis and E. coli. The increase in consumer demand and desire to consume products that reduce many health problems, including cardiovascular diseases, is one of the most important reasons that prompted the dairy industry to produce low-fat or fat-free milk products , including ice cream, by adjusting the percentage of fat or removing it according to the level required in the product as well as adding ingredients for dry structure, stabilizers, sugar and homogenization, which are important in the stability of the product and giving it strength [8]. Ice cream is one of the desired snacks by consumers, as it consists of sugars, proteins, salts, water, ice crystals, air bubbles and fat globules.…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure homogenization is an emerging and relative new technology, which is used to improve quality characteristics of dairy products up to 400 MPa pressure (Loveday et al, 2013;Massoud et al, 2016). When considering conventional homogenization, 15-60 MPa pressure are usually applied in order to ensure homogeneous distribution of milk fat, improve the consistency and stability of the product, achieve whiter colour and reduce the amount of serum separated from the yoghurt (Krebs et al, 2021). Highpressure homogenization process affects the size of milk fat globules, proteins, and polysaccharides, but it also causes the modification of their functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Highpressure homogenization process affects the size of milk fat globules, proteins, and polysaccharides, but it also causes the modification of their functional properties. Furthermore, high-pressure homogenization leads to improved properties within yoghurt matrix due to smaller and more uniform fat globules with increased surface area that incorporate into the milk proteins, casein, and denatured whey during gel formation (Krebs et al, 2021;Loveday et al, 2013;Massoud et al, 2016). Additionally, shelf-life of the products is improved by high pressure homogenization which lowers the creaming rate (Serra et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation